Penguatan Faham Fikih Ibadah Menurut Tarjih Muhammadiyah kepada Jamaah Masjid An-Nashir Pimpinan Ranting Muhammadiyah Nitikan - Niki Alma Febriana Fauzi; Qaem Aulassyahied; Muhammad Hasnan Nahar (Masyarakat Berdaya dan Inovasi, 2023)
Issues related to the practice of worship are issues that are always closely related to Muslim society. Islam makes worship a manifestation of one's faith, so If mapped, there are at least two problems that are often found in community, namely (1) the problem of authenticity and originality of the practice of worship itself, whether taught by the Prophet or not; and (2) the problem of the lack of literacy in the fiqh of worship of a community towards authoritative sources of religious teachings. Therefore, this service aims to strengthen understanding of the fiqh of worship according to Tarjih Muhammadiyah. From the above background, concerning the research and service road map of the study programme, we see that several solutions can be done, namely: (1) providing religious insights according to Muhammadiyah tarjih, as well as explaining the characteristics of Muhammadiyah fiqh to the congregation of An-Nashir Mosque; (2) providing material on fiqh of worship according to Muhammadiyah tarjih to the congregation of An-Nashir Mosque as a medium to strengthen their religious understanding. Referring to the service road map of the hadith department in UAD, this service is in the realm of Muhammadiyah Studies by taking two parts at once, namely institutional studies (in this case empowering branches and twigs) and tarjih product studies (in this context, fatwas and tarjih decisions). The two parts are combined simultaneously to strengthen the understanding of fiqh worship according to Muhammadiyah tarjih to the congregation of the An-Nashir Mosque. The hope is that this strengthening programme can realise the congregation of the An-Nashir mosque who understand the fiqh of worship according to Muhammadiyah tarjih. This service will be carried out offline or offline while still implementing health protocols.